2008
DOI: 10.1021/ol702577g
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(0)-Catalyzed Decarboxylation of Buta-2,3-dienyl 2‘-Alkynoates:  Approach to the Synthesis of 2-Alkynyl Buta-1,3-dienes

Abstract: The Pd(PPh3)4-catalyzed decarboxylation of buta-2,3-dienyl 2'-alkynoates allows the rapid construction of 2-alkynyl buta-1,3-dienes. The carbon-carbon bond-forming reaction occurs at the central position of an allene moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 46 publications
(21 reference statements)
1
8
0
Order By: Relevance
“…109 After some screening, very similar conditions to those reported by Rayabarapu and Tunge 108a were found to be useful in effecting the transformation. The reaction was quite general and tolerated rather large allenyl substituents (entry 1).…”
Section: Sp-hybridized Carbon Nucleophilessupporting
confidence: 61%
“…109 After some screening, very similar conditions to those reported by Rayabarapu and Tunge 108a were found to be useful in effecting the transformation. The reaction was quite general and tolerated rather large allenyl substituents (entry 1).…”
Section: Sp-hybridized Carbon Nucleophilessupporting
confidence: 61%
“…Notable examples of Pd-catalyzed decarboxylative coupling reactions include decarboxylative alkylation, decarboxylative Heck coupling, aldol addition, decarboxylative cross-coupling, etc. In 2008, Chung et al reported the synthesis of 2-alkynyl buta-1,3-dienes by decarboxylation of buta-2,3-dienyl 2′-alkynoates (Scheme ) . We envisioned that such a strategy of decarboxylation of allenyl 3-oxoalkanoates would allow a convenient route to dienyl or allenyl ketones via an α-methylene π-allylpalladium intermediate (Scheme ). , To the best of our knowledge, the synthesis of 3,4-allenyl ketones has not been well established: they may be prepared by the reactions of enolates or imines with the alkylating agents, usually allenic chlorides or tosylates, using a strong base at low temperature.…”
mentioning
confidence: 99%
“…46−48 This involves relatively neutral conditions and eliminates expensive and toxic organometallic reagents. 49,50 Various decarboxylative Csp 3 −Csp 3 , Csp 3 −Csp 2 , and Csp 3 − Csp couplings 51−53 have been reported to synthesize a wide range of value-added chemicals including propargylamines, 54 biaryls, 55,56 2-alkynylbuta-1,3-dienes, 57 1,4-diamino-2-butynes, 50 1,2,3-triazoles, 58 etc. Recently, we reported decarboxylative A3 and KA2 coupling strategies for one-pot multicomponent reactions to afford a wide range of propargylamines and C1-alkynylation of tetrahydroisoquinolines and N-heterocycles using CuO@Fe 2 O 3 MNPs and Cu@SiO 2 −NS as recyclable nanocatalysts, respectively.…”
Section: ■ Introductionmentioning
confidence: 67%
“…Further, the carboxylic group of amino acids opens up the possibility of site-specific functionalization via decarboxylative pathway. Transition metal-catalyzed decarboxylative coupling reaction provides an ecofriendly pathway for C–C or C–heteroatom bond formation due to in situ formation of organometallic species. This involves relatively neutral conditions and eliminates expensive and toxic organometallic reagents. , Various decarboxylative Csp 3 –Csp 3 , Csp 3 –Csp 2 , and Csp 3 –Csp couplings have been reported to synthesize a wide range of value-added chemicals including propargylamines, biaryls, , 2-alkynylbuta-1,3-dienes, 1,4-diamino-2-butynes, 1,2,3-triazoles, etc. Recently, we reported decarboxylative A3 and KA2 coupling strategies for one-pot multicomponent reactions to afford a wide range of propargylamines and C1-alkynylation of tetrahydroisoquinolines and N-heterocycles using CuO@Fe 2 O 3 MNPs and Cu@SiO 2 –NS as recyclable nanocatalysts, respectively. , To date, there are very few reports describing the decarboxylative tandem coupling among proline, aldehydes, and alkynes using Cu-salts as homogeneous catalysts. There is a need to develop efficient nanocatalysts for these decarboxylative tandem coupling reactions under green and sustainable conditions.…”
Section: Introductionmentioning
confidence: 99%